‘IRFANI EPISTEMOLOGY IN ISLAMIC PHILOSOPHY PERSPECTIVE - Syamsul Rijal; Rasyidin Muhammad (Journal Analytica Islamica, 2021)
This study tries to describe the epistemology of Irfani and formulate the Irfani method in Islamic philosophy.  In this study, the researcher used the literature review method. This study concludes that Irfani means knowledge, where this knowledge is obtained directly through experience (experiment) on religious spiritual reality. Irfani's development is divided into six phases: 1) The nursery phase. 2) Birth phase. 3) Growth phase. 4) Peak phase. 5) The specification phase 6) The decline phase. Irfani's methods andstages: a) The first stage, preparation. b) The second stage, the acceptance stage. c) The third stage, disclosure. Irfani in the perspective of Islamic Philosophy can be seen in the explanation of Muhyiddin ibn 'Arabi, who said Makrifat and this intuitive knowledge are not reached by reason and rational argumentation, but by divine guidance. Surahwardi does not consider that intuitive knowledge (read: irfani knowledge) precedes reasonable knowledge. The preamble of intuitive knowledge is the purification and enlightenment of the soul, which is a prelude to rational discussion, namely the science of logic.